STRUCTURAL-FUNCTIONAL MODEL OF FORMATION OF THE HUMANITIES SUBJECTS TEACHERS' READINESS FOR THE VOCATIONAL GUIDANCE WORK (Physical Culture and Sport: Scientific Perspective, 2023)
The relevance of the problem of forming the readiness of teachers of humanitarian subjects to conduct vocational guidance work with schoolchildren in general secondary education institutions, which is carried out starting from elementary school and ending with high school, is substantiated. The expediency of effective professionally self-determined students at school has been proven, as high results of professional activity in the future are an important strategic resource of the state and society as a whole.The definition of the concept of "teacher's readiness for vocational guidance work" is given. The content of the introduced structural-functional model is revealed and its influence on the formation of the readiness of humanities teachers to organize and conduct vocational guidance work is outlined. Within the framework of the model, all components that are interconnected and interdependent and constitute four blocks are substantiated: the target, during which the formation of educational, developmental and educational readiness takes place; theoretical as conceptualizing, which includes the conceptual and categorical apparatus, didactic general-pedagogical and specific principles, scientific approaches, theories and methods, levels of structuring of the content of the teacher's vocational guidance work, the position of humanitarian and vocational guidance knowledge; procedural-methodical with four main components of a teacher's readiness to conduct vocational guidance work - motivational-value, substantive-operational, evaluative-reflective and professional-developmental for the implementation of the proposed pedagogical conditions; result-evaluative, which is represented by the levels of professional readiness, obtained with the help of mathematical statistics methods, as a result of the formed readiness of teachers for vocational guidance work with students in secondary schools.It was concluded that the introduction of the structural-functional model into the process of training teachers of humanities subjects creates suitable conditions for the formation of teachers' readiness to conduct vocational guidance work with students in secondary schools.
Keywords: teachers of humanitarian subjects; students; vocational guidance work; institutions of general secondary education; structural-functional model; readiness for vocational guidance